Editorial for the Special Issue “Physical Medicine and Rehabilitation: Trends and Applications” - Karen Sui Geok Chua; Krisna Piravej; Jiunn-Horng Kang; Li-Wei Chou (Life)
Physical medicine and rehabilitation blend scientific expertise with compassionate care to enhance quality of life and restore functionality for individuals with complex conditions [...]